PENGEMBANGAN LKS DENGAN PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS LIFE SKILLS MATERI BANGUN RUANG - Wasilatul Murtafiah (IKIP PGRI MADIUN, 2014)
Orientation: life skills education has become one of the government's policy in the field of education. Implementing life skills education in the learning process, schools need to prepare oriented curriculum to life skills education. Achievement of these life skills must be specifically designed not just as an accompaniment destination (by chance). One of the mathematics learning approaches that link reallifeexperiences of students with mathematics material is Realistic Mathematics Education (RME). Research purpose: develop student worksheets with Realistic Mathematics Education (RME) based life skills that meet the criteria of validity on the solid material. Research design, approach and method: this type of research is development research. Development of Student Worksheet in this research refers to the 4-D models by Thiagarajan, et al which has been adjusted. The phase 4-D models are used only three stages are comprised of: define, design, and develop. This research was conducted in class VIII-C SMP Negeri 2 Kwadungan Ngawi. Main Findings: learning device test results obtained are categorized of Student Worksheet is valid, because it meets the requirements set out, namely: (1) the category of expert validation is valid, (2) the category of students readability test is valid, and (3) the category of students response is positive.